Universities’ Research Performance: Evaluation Issues - Reheilo, Iryna; Bazeliuk, Nataliia (Pedagogical Discourse, 2021)
The need to review the universities’ research performance evaluation, which is based on scientometric indicators is raised in the paper. The attention is drawn to an objective understanding of university rankings, which in many countries are the basis for financial support of higher education institutions without taking into account their successful implementation of regional and national social needs. The Ukrainian regulative requirements concerning scholarly publishing in the Scopus and Web of Science citation databases of the faculty, higher education institutions research performance, research journals functioning are given. The dynamics and presentation of the Ukrainian classical and pedagogical universities scholarly publishing in the research area of Education and Educational Research during 2016–2020 covered by the Web of Science Core Collection database is analysed. The specifics of the Social Sciences and Humanities, which should be considered during the development of effective methods and innovative approaches of universities research performance evaluation, is enlightened, in particular, the importance of monographs and books; pronounced national and regional significance; citing culture giving the medium and long term perspective of the Social Sciences and Humanities conceptual bases; multilingualism of publications; the importance of translating publications to achieve open access; interdisciplinary nature of research; predominance of single authorship; ensuring objective research performance evaluation within one field, creation of a polycentric multilingual research evaluation system.